Non-Gaussian limit distributions of solutions of the many-dimensional Bürgers equation with random initial data - Li, Zhanbing; Leonenko, N. N.; Rybasov, K. V. (Ukrains’kyi Matematychnyi Zhurnal, 1995)
Limit distributions of solutions of the multidimensional Bürgers equation are found in the case where an initial condition is a random field of type χ2 of degreek with a long-range dependence.